Radikalisme Agama, Tinjauan Sosial Politik - Asep Saeful Muhtadi (FISIP UIN SGD Bandung, 2018)
This article examines some phenomena of religious radicalism ended in violence and frequently caused massive physical and psychological victims. The phenomena of radicalism could be analyzed involving various variables, like social, political, economic, including cultural variables. The tragedy of Cikeusik was a kind of violence emerged from subjective religious interpretation, exclusivism, and external political situation. Outside those factors, the weak of the “state” in preventing conflicts and being a significant contributor.